Heavy metal loads in the soil of Debrecen - Szegedi, Sándor (Acta Geographica Debrecina Landscape & Environment series, 2007)
Results of examinations on the amount, and spatial distribution of heavy metal compounds in the soil of Debrecen, their geographic, pedologic and ecologic aspects are presented in this study. The effects of the differences in traffic conditions, build-up/land use and the density of vegetation on the heavy metal content of the soils have been examined in city of Debrecen and its closer environment. Cadmium-, cobalt-, nickel-, lead-, and copper-contents of the soil samples taken from 88 sites of the sample area have been studied after acidic extraction, using atomic absorption spectrometer with the flame technique. Close-to-background concentrations of heavy metals in unpolluted soils of the forested area of the Nagyerdő were determined. Spatial differences in the heavy metal content of the soils for the whole area of Debrecen have been studied. Influence of soil properties (humus, CalciumCarbonate content, pH and grain size distribution) on the binding and mobility of heavy metals in the soil has been examined. Vertical distribution and mobility of heavy metal compounds in acid sandy soils was determined. Heavy metal content of soil in the most sensitive areas, playgrounds, recreational areas, urban gardens and grazing fields along busy roads has been surveyed.